2019
DOI: 10.1093/advances/nmy116
|View full text |Cite
|
Sign up to set email alerts
|

Food Choices of Young Adults in the United States of America: A Scoping Review

Abstract: Understanding food choice is critical to developing effective health promotion efforts to counter the leading causes of morbidity and mortality in the United States. Although physiologic, environmental, and social factors influence the development of health conditions, routine decisions, such as food choice, also contribute substantially over time. Behavioral scientists believe that these routine decisions represent a key opportunity to improve population health. We conducted a scoping review of both health an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 42 publications
2
24
0
1
Order By: Relevance
“…As over 50% of young Australian adults aged 18–30 years are overweight or obese [ 1 ], poor diet is considered the leading risk factor for disease in this age group [ 2 , 3 ]. To improve the diet and health of young adults, it is first necessary to understand the influences on their food choice [ 4 ]. Within the framework described by Furst et al [ 5 ], life course influences, such as personal and social influences, and value negotiations, such as sensory perceptions and health and nutrition, shape food choice and intake.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As over 50% of young Australian adults aged 18–30 years are overweight or obese [ 1 ], poor diet is considered the leading risk factor for disease in this age group [ 2 , 3 ]. To improve the diet and health of young adults, it is first necessary to understand the influences on their food choice [ 4 ]. Within the framework described by Furst et al [ 5 ], life course influences, such as personal and social influences, and value negotiations, such as sensory perceptions and health and nutrition, shape food choice and intake.…”
Section: Introductionmentioning
confidence: 99%
“…Young adulthood is a life stage characterized by life transitions, including becoming responsible for food purchasing and preparation [ 4 ]. The transition to university has been shown to negatively impact on food choices, particularly among those who live away from home [ 15 , 16 , 17 , 18 ]; thus, these changes may disproportionately influence the relationship between food liking and food intake.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A scoping review of food choice amongst young adults in the USA identified similar general patterns, highlighting that snacking, rather than consuming three meals, is a popular behaviour in this age group, as observed in our Snackers and Grab-and-Go patterns. Additionally they observe that 'healthy' food items can be a driver of food choice in some, which we can see in the Vegetarian and Dieters clusters (35) .…”
Section: Overall Dietary Patternsmentioning
confidence: 80%
“…In compliance with the methodology of the discrete choice experiment, this was preceded by a qualitative procedure (focus group interviews with two groups of Hungarian and two groups of international students with eight participants by each group in September 2019). We chose students in higher education as a target group since they had been found to have extremely disparate divergent behaviour in terms of health awareness in several studies (Yahia et al, 2008;Al-Rethaiaa et al, 2010;Abraham et al, 2018;Kyrkou et al, 2018;Sogari et al, 2018;Alkazemi, 2019;Powell et al, 2019). By supplementing the results of the focus group interviews with knowledge gained from the literature, we defined the product attributes to be examined in the research.…”
Section: Methodsmentioning
confidence: 99%